Offshoring and Job Polarisation between Firms - Hartmut Egger; Udo Kreickemeier; Christoph Moser; Jens Wrona (Center for Economic Studies and ifo Institute (CESifo), 2016)
We set up a general equilibrium model, in which offshoring to a low-wage country can lead to job polarisation in the high-wage country. Job polarisation is the result of a reallocation of labour across firms that differ in productivity and pay wages that are positively linked to their profits by a rent-sharing mechanism. Offshoring involves fixed and task-specific variable costs, and as a consequence it is chosen only by the most productive firms, and only for those tasks with the lowest variable offshoring costs. A reduction in those variable costs increases offshoring at the intensive and at the extensive margin, with domestic employment shifted from the newly offshoring firms in the middle of the productivity distribution to firms at the tails of this distribution, paying either very low or very high wages. We also study how the reallocation of labour across firms affects economy-wide unemployment. Offshoring reduces unemployment when it is confined to high-productivity firms, while this outcome is not guaranteed when offshoring is also chosen by low-productivity firms.
Keywords: F12; F16; F23; 330; offshoring; job polarisation; heterogeneous firms; unemployment